2007
DOI: 10.1007/s12079-007-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 (Connective Tissue Growth Factor) is essential for extracellular matrix production and integrin signaling in chondrocytes

Abstract: The matricellular protein CCN2 (Connective Tissue Growth Factor; CTGF ) is an essential mediator of ECM composition, as revealed through analysis of Ccn2 deficient mice. These die at birth due to complications arising from impaired endochondral ossification. However, the mechanism(s) by which CCN2 mediates its effects in cartilage are unclear. We investigated these mechanisms using Ccn2−/− chondrocytes. Expression of type II collagen and aggrecan were decreased in Ccn2 −/− chondrocytes, confirming a defect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 84 publications
2
83
0
Order By: Relevance
“…In chondrocytes, CTGF regulates ECM via ERK1/2 signaling (Nishida et al, 2007). Our study shows that QC reduces TGFb1-induced effects; the expression of MMPs and ERK is down-regulated.…”
Section: Discussionmentioning
confidence: 55%
“…In chondrocytes, CTGF regulates ECM via ERK1/2 signaling (Nishida et al, 2007). Our study shows that QC reduces TGFb1-induced effects; the expression of MMPs and ERK is down-regulated.…”
Section: Discussionmentioning
confidence: 55%
“…Next, we determined whether the binding of CCN2 to cognate integrin receptors explains its anti-catabolic effects. We used disintegrins ECH and VLO4 to inhibit CCN2-specific, RGD-dependent integrins ␣v␤3 and ␣5␤1, respectively (10,12,26). First, we confirmed that these disintegrins block CCN2 function by measuring aggrecan expression with or without ECH and VLO4 in NP cells following CCN2 treatment.…”
Section: Anti-catabolic Effect Of Ccn2 Is Independent Of Nf-b Modulatmentioning
confidence: 61%
“…Thus, given that the NF-B is a major downstream effector of inflammatory stimuli; it is likely that in the healthy NP, in contrast to other cell types, CCN2 is primarily anabolic and unlikely to play an inflammatory role (19,44). Next, we investigated the possibility that the anti-catabolic effects of CCN2 are mediated through cognate integrin receptors, ␣5␤1 and ␣V␤3 (10,12,41). We tested this possibility using the disintegrins ECH and VLO4 to inhibit ␣v␤3 and ␣5␤1, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon stimulation, CTGF is secreted into the extracellular environment, where it interacts with distinct cell surface receptors, growth factors, and the extracellular matrix (ECM) (34). The principal CTGF receptor is the heterodimeric cell surface integrin complex whereas integrin-linked kinase (ILK) is a key mediator of integrin signaling that interacts with the cytoplasmic domain of ␤ integrins (22,25,40). Activated ILK subsequently phosphorylates AKT, also known as protein kinase B and glucose synthesis kinase-3 ␤ (GSK-3␤) thus leading to activation of a diverse array of cellular processes (22,37,45).…”
mentioning
confidence: 99%